Themes and methodological issues in Court Interpreting research - Hale, Sandra (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
The field of Legal Interpreting encompasses a wide variety of contexts including police interviews and interrogations, lawyer-client conferences, tribunal and court hearings and trials. Most of the research carried out in the field to date has concentrated on the discourse of the courtroom in Common Law countries (Berk-Seligson 1988, 1990, 1999; Hale 1997b, 1999, 2004; Mason & Stewart 2001; Pym, 1999; Rigney 1997). This is partly due to the availability of the data, as most courtrooms are open to the public, but also due to the vast amount of research conducted into the language of the courtroom, which has served as a theoretical basis for the study of court interpreting. These studies draw on discourse analysis, the ethnography of language, pragmatics, experimental psychology and forensic linguistics to inform their methods. Other research into legal interpreting has looked at other , non-linguistic aspects of the practice, such as role perceptions and expectations, using social science methods of surveys, interviews and focus groups (Fowler 1997; Kelly 2000; Hale & Luzardo 1997; Angelelli 2004). Fewer studies have concentrated on the other aspects of legal interpreting, such as police interpreting (Krouglov 1999; Berk-Seligson 2000; Russell 2004; Wadensjš 1997) and tribunal hearings (Wadensjš 1992; Mason & Stewart 2001; Barsky 1996). With the exception of a limited number of experimental studies (Berk-Seligson 1990 and Hale 2004) most legal interpreting research studies have been descriptive, qualitative and speculative, providing useful information on the current state of affairs but little on the impact such practices have on the legal process. This contribution will concentrate only on court interpreting research. It will review the major research projects to date, highlight their strengths and weaknesses, identify the gaps that exist in our knowledge of the field andproposefurther research studies tofill such gaps.